Fitness & wellness - Hoeger, Werner W. K.; Hoeger, Sharon A.; Hoeger, Cherie I. (Cencage, 2019)
Take control of your health--and life--with FITNESS AND WELLNESS. Reflecting the latest research and practical guidelines on nutrition, fitness and disease prevention, the 13th Edition equips you with the tools you need to make positive choices for your health. After assessing your current habits, you soon will be following the book's easy steps to start positive behavior changes. Hands-on activities let you immediately apply what you learn to your own life, while engaging visuals and descriptive examples in each chapter help you visualize key concepts. A wealth of online resources extend your learning beyond the classroom and reinforce key concepts through behavior modification planning activities, practice tests, online labs and a behavior change planner. Empower yourself to make positive changes and improve your health with FITNESS AND WELLNESS